Strengthening Family Resilience through the Tradition of Agricultural Zakat Payment in Nagari Lima Kaum in Tanah Datar District of West Sumatera - Elimartati, Elimartati; Fahlefi, Rizal; Erniyanti, Liza (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Family resilience is a crucial factor to support community resilience, which later leads to the resilience of the nation and state. This study describes and analyzes family resilience through the use of agricultural zakat in Nagari Lima Kaum, Tanah Datar in West Sumatra. This study is empirical or sociological legal research that perceives law as a social phenomenon. Data collection techniques include interview and document study. This study concludes that the uniquetradition of paying zakat carried out by the local community in Nagari Lima Kaum known as basokek can strengthen family resilience. As seen from the accounting of zakat, while most of the muzakki belong to underprivileged community, they always issue zakat rice because this has been a religious tradition for generations believing that they must pay zakat. This tradition, however, tends to be abandoned, yet the essence of the practice is still carried out today. The zakat practice includes distributing payment of zakat rice to the poor, the needy, old widows, mosques, and even people who are studying. In overview, zakat is an activity aimed to increase piety to Allah s.w.t for the muzakki and fulfill basic needs for the mustahiq in realizing family resilience in the social and economic fields.